2014
DOI: 10.1002/smi.2565
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Recovery Responses during a 105‐day Ground‐based Space Simulation

Abstract: The present study analysed the time course of the psychological process of stress and recovery in six healthy male volunteers during the Mars 105 experimentation, a 105-day ground-based space analogue. The multidimensional assessment of stress and recovery responses showed that stress levels decreased significantly throughout the 105-day isolated and confined extreme (ICE) experiment, especially on its social dimension. In line with previous studies, Fatigue showed a global and progressive reduction. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
(54 reference statements)
1
9
0
Order By: Relevance
“…Several studies of small groups in other isolated environments suggest that prolonged isolation and confinement leads to interpersonal issues and increased social tension (for reviews, see Leon et al, 2011; Palinkas & Suedfeld, 2008; Zimmer, Cabral, Borges, Côco, & Hameister, 2013). These findings are also in agreement with other recent studies in space analogues, the WISE 2005 study, a 60-day head-down tilt long-term bed rest (HDTBD; Nicolas, 2009), and the Mars 105 experiment (Nicolas & Gushin, 2015). Both showed that the social dimension is a key factor in adaptation, especially during prolonged ICE missions that pose difficulties for the participants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several studies of small groups in other isolated environments suggest that prolonged isolation and confinement leads to interpersonal issues and increased social tension (for reviews, see Leon et al, 2011; Palinkas & Suedfeld, 2008; Zimmer, Cabral, Borges, Côco, & Hameister, 2013). These findings are also in agreement with other recent studies in space analogues, the WISE 2005 study, a 60-day head-down tilt long-term bed rest (HDTBD; Nicolas, 2009), and the Mars 105 experiment (Nicolas & Gushin, 2015). Both showed that the social dimension is a key factor in adaptation, especially during prolonged ICE missions that pose difficulties for the participants.…”
Section: Discussionsupporting
confidence: 92%
“…An appropriate level of stress can improve adaptive responses to constraining or extreme situations (Palinkas, 1992). However, excessive levels or ineffective regulation of stress in ICE could generate dysfunctional adaptation, with detrimental outcomes both in crews’ well-being and performance (Geuna & Brunelli, 1995; Nicolas & Gushin, 2015; Nicolas & Weiss, 2009). For organizations involved in Antarctic operations, such knowledge of potential stressors (physical, emotional, social, and behavioral), recovery regulation, and defense mechanisms (DM) would be useful in two ways: to improve the selection of personnel and to identify countermeasures that could help crews cope with these constraining conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Stress and coping strategies (cognitive and behavioural resources to deal with stressful situations [Folkman & Moskowitz, 2004]) are frequently studied in Antarctic research yet no consensus has been reached. Some studies observed increased stress towards the end of an annual expedition (Nicolas & Gushin, 2015). Others found that coping strategies decreased during the midwinter period, as opposed to the established view in favor of the use of more active strategies under chronic stress conditions (Sandal, van deVijver, & Smith, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive coping strategies were associated with mature defence mechanisms, while less adaptive coping strategies were linked to symptoms of depression (Nicolas et al, 2013). Accordingly, immature defence mechanisms were positively correlated with total stress and perceived stress during a prolonged confinement period (Nicolas & Gushin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…That may be due to the existence of complex human body adaptation mechanisms that sustain or restore homeostasis in response to a simulated microgravity environment. Numerous studies have evoked energy related recovery‐stress states (Nicolas & Gushin, 2015; Nicolas & Weiss, 2009), cardiovascular (Platts et al., 2009; Rabineau et al., 2020) and skeletal (Hu et al., 2014; Rubin et al., 2002) adaptation mechanisms as a reaction to microgravity. Moreover, previously documented RSL‐related adaptation trends, encountering microgravity effects, include the preservation of lean body mass, prevention of partial cardiac deconditioning (Kramer, Gollhofer, et al., 2017), the structure of the skeletal muscle, preservation of phenotype and oxidative potential of the myofibres (Blottner et al., 2020).…”
Section: Discussionmentioning
confidence: 99%